Pulmonary artery banding for dilated cardiomyopathy in children: report of 3 cases - Linghan Meng; Qingyu Gao; Zhanhui Du; Ping Yang; Lijuan Zong; Bei Lv; Quansheng Xing (BMC Pediatrics)
Abstract Background Pulmonary artery banding (PAB) has emerged as a promising surgical treatment for pediatric dilated cardiomyopathy (DCM) in recent years. However, clinical evidence supporting its efficacy remains limited. This study reports on three cases with DCM treated with PAB to evaluate its short-term therapeutic outcomes. Case presentation Clinical data were collected from three children diagnosed with DCM and admitted to our hospital. Case 1 had congenital aortic arch hypoplasia (AAH) and developed progressive left ventricular (LV) enlargement in infancy. Case 2 and case 3 were initially diagnosed with endocardial fibroelastosis (EFE). All three patients had previously received standard medical therapy, but experienced progressive cardiac enlargement and declining function. Preoperative left ventricular ejection fraction (LVEF) was 25% in Case 1, 21% in Case 2 and 44% in Case 3. Each patient underwent preoperative echocardiography and cardiac magnetic resonance imaging (CMR), following by surgical PAB and postoperative monitoring. All three children were discharged in stable conditions and demonstrated favorable short-term recovery. Case 1 and 3 exhibited improvements in LVEF of over 20% compared to preoperative values, along with reversal of left heart - suggesting the potential for myocardial reverse remodeling. Case 2 showed marginal improvement with stabilization of LV dilation during follow-up of 4-months. Conclusion Pulmonary artery banding appears to be a valuable therapeutic option for pediatric DCM, particularly in patients where heart transplantation or mechanical circulatory is not feasible. Further studies with larger cohorts and longer follow-up are needed to confirm its long-term efficacy. Clinical trial number Not applicable.